Text, speech, and dialogue : 18th International Conference, TSD 2015, Pilsen,Czech Republic, September 14-17, 2015, Proceedings - Král, Pavel; Matoušek, Václav (Lecture Notes in Computer Science, 2015)
This book constitutes the refereed proceedings of the 18th International Conference on Text, Speech and Dialogue, TSD 2015, held in Pilsen, Czech Republic, in September 2015. The 67 papers presented together with 3 invited papers were carefully reviewed and selected from 138 submissions. They focus on topics such as corpora and language resources; speech recognition; tagging, classification and parsing of text and speech; speech and spoken language generation; semantic processing of text and speech; integrating applications of text and speech processing; automatic dialogue systems; as well as multimodal techniques and modelling.